An analysis of trends and determinants of child undernutrition in Ethiopia, 2000‐2011 - Headey, Derek D. (International Food Policy Research Institute, 2014)
This report uses two rounds of the Ethiopian Demographic Health Survey (EDHS) to statistically analyze patterns and trends in undernutrition (child growth) in Ethiopia over 2000 to 2011. Ethiopia remains one of the most undernourished populations in the world. In 2000 over half of Ethiopian preschool children were stunted (height for age z-scores (HAZ) of -2 standard deviations or less) and almost a third were severely stunted (HAZ ≤ -3.0). However, progress against child undernutrition over this period has been solid, with stunting prevalence reduced by 1.4 percent points per year between 2001 and 2011, although progress slowed to 1.0 point per year between 2011 and 2014.